2021
DOI: 10.1038/s41598-021-84492-3
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase engineered lipid nanovesicles for the treatment of triple negative breast cancer

Abstract: In the field of oncology research, a deeper understanding of tumor biology has shed light on the role of environmental conditions surrounding cancer cells. In this regard, targeting the tumor microenvironment has recently emerged as a new way to access this disease. In this work, a novel extracellular matrix (ECM)-targeting nanotherapeutic was engineered using a lipid-based nanoparticle chemically linked to an inhibitor of the ECM-related enzyme, lysyl oxidase 1 (LOX), that inhibits the crosslinking of elastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…These investigations could provide more guidance for future potential pre-clinical or clinical studies. Additionally, we will investigate the application of our anti-CD47 mAb for targeted drug delivery via liposomes or other nanoparticles [ 62 , 63 , 64 ] for TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations could provide more guidance for future potential pre-clinical or clinical studies. Additionally, we will investigate the application of our anti-CD47 mAb for targeted drug delivery via liposomes or other nanoparticles [ 62 , 63 , 64 ] for TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment (TME) refers to the surrounding micro-environment where tumor cells exist, including surrounding blood vessels, immune cells, fibroblasts, bone marrow-derived inflammatory cells, various signaling molecules, and extracellular matrix (ECM) (44). In various tumors, overexpression of LOX induced by a hypoxic (45). Targeting LOX family-mediated matrix cross-linking as an anti-matrix therapy for solid tumors (46).…”
Section: Discussionmentioning
confidence: 99%
“…Saatci et al demonstrated that targeting LOX can overcome chemotherapy resistance in triple-negative breast cancer ( 4 ). De Vita et al reported: Lysyl oxidase engineered lipid nanovesicles for the treatment of triple-negative breast cancer ( 45 ). Targeting LOX family-mediated matrix cross-linking as an anti-matrix therapy for solid tumors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of biomaterials, ECM mechanical cues have been shown to participate in proliferation, survival, spread and motility of ECs through mechanotransduction mediated by integrins and the following phosphorylated FAK and paxillin (PXN) [ 15 , [21] , [22] , [23] , [24] ]. ECM stiffens in many pathological processes, including cancer and wound healing [ 25 , 26 ], which remarkably promotes angiogenic outgrowth and branching of ECs [ 27 ]. Moreover, rigid ECM can activate YAP in a Hippo/LATS-cascade-independent manner [ 28 ].…”
Section: Introductionmentioning
confidence: 99%